Motivations for Equity Borrowing: A Welfare-switching Effect - Wood, Gavin; Parkinson, S.; Searle, B.; Smith, S. (Hindawi Publishing Corporation, 2013)
During the early 2000s, mortgage market innovation together with home price appreciation increased the scope for mortgage equity withdrawal. From a macroeconomic perspective, this proved to be an important transmission mechanism for the wealth (particularly collateral) effects of housing. Microeconomic accounts of equity borrowing are less well developed, since standard models of savings and consumption rarely take housing wealth into account. This paper, however, builds on a small but growing literature assigning a precautionary savings role to consumption from housing wealth. The analysis uses panel data sourced from Britain and Australia to model households’ motivations for equity borrowing. Key among these motivations are pressing, uninsurable, ostensibly short-term, spending needs. In these contexts, it is proposed that equity borrowing assumes a welfare-switching role, substituting privately owned housing wealth for collectively funded safety-nets.